Kansallismaisema : Metsäkukkia 2024:installaatio: kierrätyspaperi, puurima, pellettibriketit - Huhmarniemi, Maria (Lapin taiteilijaseura, 2024)
Kansallismaisema-näyttelyn teema perustuu ihmisten metsäsuhteisiin Suomessa. Me olemme tottuneet katsomaan etäällä siintävää järveä hakkuuaukkojen reunoilla. Puita on mittailtu katseella hakkaamisen tuloja laskien. Harvinaisten luontotyyppien suojelumääräyksiä kierretty ja Lapin metsien päätymistä selluksi Kiinaan juhlittu. Näyttelyssä on esillä installaatiota. Huhmarniemi käyttää kierrätyspaperia Metsäkukkiateoksessaan, joka viittaa puupeltoihin ja selluteollisuuteen. Kolmen taiteilijan - Maria Huhmarniemen, Johannes Pekosen ja Tommi Yläjoen - yhteistyö kiinnittyy pohjoismaiseen Observation of Change -taidehankkeeseen, jossa tarkastellaan taiteen keinoin metsäluonnon ennallistamista Junkerdalin luonnonsuojelualueella Pohjois-Norjassa. The theme of the National Landscape exhibition is people's relationships with forests in Finland. We like to look at a distant lake from the view opened by cutting trees. Forests are seen as profits from logging. Conservation regulations for rare habitat types are not respected, and pulp export abroad is celebrated. The exhibition features installations. Huhmarniemi uses recycled paper in her artwork "Forest Flowers," which refers to industrial forest fields and the pulp industry. Pekonen addresses the contradiction in which he condemns the natural resource extraction while also relying on its products. The orange plastic handle of a hand saw in Yläjoki's work adds colour to the exhibition's dark tone. The collaboration of the three artists - Maria Huhmarniemi, Johannes Pekonen, and Tommi Yläjoki - is linked to the Nordic "Observation of Change" art project, which examines, through art, the restoration of forest nature in the Junkerdal Nature Reserve in Northern Norway. The artworks: Maria Huhmarniemi, "Forest Flowers," installation: recycled paper, wooden frames, pellet briquettes, 2024. Tommi Yläjoki, "In the Clearing," sculpture, wood, metal, plastic-handled hand saw, 2024. Johannes Pekonen, "Saw: Turn the Crank and Look Through the Saw to See What Building This Work ...